Effective Strategies to Increase Student Physical Activity through Social Media - Zainuddin, M. Said; Usman, Arifuddin; Zakaria, Ahmad (Sahabat Publikasi Kuu, 2024)
This study investigates the role of social media in promoting physical activity among university students at FIKK Negeri Makassar, addressing a concerning trend of insufficient exercise levels linked to academic pressures and sedentary lifestyles. A survey of 339 students revealed that many spend excessive hours on laptops, leading to fatigue and low motivation for physical activity, which poses risks for obesity and mental health issues. The purpose of this initiative is to leverage social media platforms to raise awareness about the importance of physical activity and encourage students to integrate it into their daily routines.The methodology involves identifying the target group, collecting data through surveys, and creating engaging educational content featuring healthcare professionals discussing the benefits of exercise. Findings indicate that targeted social media campaigns can effectively reach students and motivate them to adopt healthier lifestyles. The results demonstrate a positive correlation between social media engagement and increased awareness of physical activity's benefits. In conclusion, this initiative highlights the transformative potential of social media in shaping health behaviors among university students, emphasizing the need for continuous evaluation to refine strategies and maximize impact on student health outcomes.